Diseño del asiento anura enfocado en la representación simbólica de la cultura Quillacinga para la personalización de espacios habitables (2020)
The cultural history of the Quillacinga crafting, has faede over time, as very few documents registered their way to work with timber, so there is not a record of their different craftsman techniques, so the opportunity to develop a new aesthetic proposal in the furniture from the design of the Anura seat that allows the personalization of a space and in this way the rescue, preservation and dissemination of different knowledge originating in the community from the perspective of industrial design, where it was developed A personalized artifact that represents the culture and techniques such as MOPA - MOPA and GUANGA, originating from the council, and also responsible terms and methodologies take root with the product design cycle under guidelines in the value chain as a process to create the artifact.